Polytetrafluoroethylene composite material and preparation method thereof
By using sulfuric acid and phosphoric acid compound acidified and modified petroleum coke powder as fillers, the wear resistance of polytetrafluoroethylene materials is significantly improved, the problem of insufficient wear resistance is solved, and the life span is extended and the cost is reduced.
Patent Information
- Application Number
- CN202510167204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-15
- Publication Date
- 2025-04-25
AI Technical Summary
The wear resistance of polytetrafluoroethylene materials is poor, resulting in a short life in long-term high-speed operation conditions and frequent replacements lead to high costs.
The modified petroleum coke powder is acidified by acidizing the composite acid made of sulfuric acid and phosphoric acid, and modified in a modified solution composed of isooctyl acrylate, bisphenol A diallyl ether, phenyl tris(dimethylsiloxane)silane and toluene. The obtained modified petroleum coke powder is combined with polytetrafluoroethylene as a filler, which significantly improves its wear resistance.
The wear resistance of polytetrafluoroethylene materials is significantly improved, which extends its life and reduces replacement frequency and cost.
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a polytetrafluoroethylene composite material and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene material has excellent chemical stability, aging resistance, radiation resistance, thermal stability, etc., and polytetrafluoroethylene has a low friction coefficient and is one of the main raw materials for self-lubricating sealing materials.
[0003] However, the wear resistance of polytetrafluoroethylene material itself is relatively poor. Its wear resistance is mainly reflected by its low friction coefficient, which reduces system wear. However, in long-term high-speed operation conditions, the wear resistance of polytetrafluoroethylene is difficult to meet the demand, resulting in its short life. The cost of polytetrafluoroethylene material is relatively high, and frequent replacement leads to high costs.
[0004] In the prior art, in order to improve the wear resistance of polytetrafluoroethylene, fillers that improve the wear resistance, such as calcium carbonate whiskers, are usually added. Although the wear resistance of polytetrafluoroethylene materials can be improved to a certain extent by adding fillers, the improvement is limited. The life of polytetrafluoroethylene materials is still short and it is difficult to meet the needs of various special application scenarios. Therefore, there is still room for improvement. Summary of the invention
[0005] In order to further improve the wear resistance of polytetrafluoroethylene and thus increase its service life, the present application provides a polytetrafluoroethylene composite material and a preparation method thereof.
[0006] In a first aspect, the present application provides a polytetrafluoroethylene composite material, which adopts the following technical solution: A polytetrafluoroethylene composite material, comprising the following components in parts by weight: 50-60 parts of polytetrafluoroethylene; 20-26 parts of modified petroleum coke powder; 20-24 parts of filler; The modification method of the modified petroleum coke powder is as follows: Step 1), adding petroleum coke powder into a composite acid for acidification, filtering, and obtaining acidified petroleum coke powder; Step 2), adding the acidified petroleum coke powder into the composite modification liquid, filtering, and drying to obtain modified petroleum coke powder; The composite acid is a compound of sulfuric acid and phosphoric acid; The composite modified liquid is a compound of isooctyl acrylate, bisphenol A bisallyl ether, phenyl tris(dimethylsiloxane) silane and toluene.
[0007] By adopting the above technical scheme, the petroleum coke powder is acidified by using a composite acid prepared by sulfuric acid and phosphoric acid, so that the surface of the petroleum coke powder has reactive functional groups, and then the acidified petroleum coke powder is specially modified in a composite modification liquid prepared by mixing isooctyl acrylate, bisphenol A bisallyl ether, phenyl tri(dimethylsiloxy)silane and toluene. The obtained modified petroleum coke powder can significantly improve the wear resistance of polytetrafluoroethylene materials, so that the service life of the polytetrafluoroethylene materials is significantly extended.
[0008] Preferably, in the composite acid, the mass ratio of sulfuric acid to phosphoric acid is 7-8:2-3.
[0009] By adopting the above technical scheme and specifically selecting the mass ratio of sulfuric acid and phosphoric acid, the acidification effect is better, the modification effect of the acidified petroleum coke powder in the modification liquid is better, and the modified petroleum coke powder has a better effect of improving the wear resistance of the polytetrafluoroethylene material.
[0010] Preferably, in the composite modified liquid, the mass ratio of isooctyl acrylate, bisphenol A bisallyl ether, phenyl tris(dimethylsiloxy)silane, and toluene is 1-1.2:1.8-2:1-2:25-30.
[0011] By adopting the above technical scheme and specifically selecting the mass ratio of isooctyl acrylate, bisphenol A bisallyl ether and phenyl tri(dimethylsiloxy)silane, the modification effect on petroleum coke powder is better, the wear resistance of the polytetrafluoroethylene material is better, and the service life is longer.
[0012] Preferably, the filler is a compound of calcium carbonate whiskers and zinc oxide whiskers.
[0013] By adopting the above technical scheme, by specifically selecting the compound of calcium carbonate whisker and zinc oxide whisker, and combining them with modified petroleum coke powder, the effect of improving the wear resistance of polytetrafluoroethylene is better, and the service life of the polytetrafluoroethylene material is extended.
[0014] Preferably, the mass ratio of the calcium carbonate whiskers to the zinc oxide whiskers is 19-22:1-2.
[0015] By adopting the above technical scheme and specifically selecting the mass ratio of calcium carbonate whiskers and zinc oxide whiskers, the effect of combining with modified petroleum coke powder is better, and the effect of improving the wear resistance of polytetrafluoroethylene materials is better.
[0016] Preferably, in the step 1), after the petroleum coke powder is put into the composite acid, the temperature is kept at 40-50° C. and the mixture is soaked and acidified for 4-6 hours.
[0017] By adopting the above technical solution and carrying out acidification at 40-50° C., the acidification effect is better, and the modified petroleum coke powder can better improve the wear resistance of polytetrafluoroethylene.
[0018] Preferably, in the step 2), the acidified petroleum coke powder is put into the composite modification liquid, and then the temperature is kept at 70-80° C. and the modified liquid is immersed for 12-14 hours.
[0019] By adopting the above technical solution and carrying out the modification at 70-80°C, the modification effect is better and the effect of improving the wear resistance of the polytetrafluoroethylene material is better.
[0020] In a second aspect, the present application provides a method for preparing a polytetrafluoroethylene composite material, using the following technical solution: A method for preparing the above-mentioned polytetrafluoroethylene composite material comprises the following steps: Step 01), polytetrafluoroethylene, modified petroleum coke powder and filler are uniformly mixed to obtain a premix; Step 02), the premix is subjected to cold pressing to obtain an embryo body; Step 03), sintering the embryo at 330-380°C and cooling to obtain a polytetrafluoroethylene composite material.
[0021] By adopting the above technical solution, the obtained polytetrafluoroethylene composite material has excellent wear resistance, long service life, effectively reduces costs, has high economic value, and well meets the needs of various special application scenarios.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application uses a composite acid formed by sulfuric acid and phosphoric acid to acidify the petroleum coke powder, the surface of the petroleum coke powder can have reactive functional groups, and the acidified petroleum coke powder is specially modified in a composite modification liquid formed by isooctyl acrylate, bisphenol A bisallyl ether, phenyl tri(dimethylsiloxy)silane, and toluene. The obtained modified petroleum coke powder can significantly improve the wear resistance of the polytetrafluoroethylene material, thereby significantly extending the service life of the polytetrafluoroethylene material.
[0023] 2. In the present application, it is preferred to specifically select the mass ratio of sulfuric acid and phosphoric acid so as to achieve a better acidification effect, so that the acidified petroleum coke powder has a better modification effect in the modification liquid, and the modified petroleum coke powder has a better effect in improving the wear resistance of the polytetrafluoroethylene material.
[0024] 3. In the present application, preferably, by specifically selecting the mass ratio of isooctyl acrylate, bisphenol A bisallyl ether, and phenyl tri(dimethylsiloxane) silane, the modification effect on petroleum coke powder is better, the wear resistance of the polytetrafluoroethylene material is better, and the service life is longer. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] Example 1 A polytetrafluoroethylene composite material comprises the following components: Polytetrafluoroethylene, modified petroleum coke powder, filler.
[0027] Polytetrafluoroethylene was purchased from Daikin, Japan, brand: F-303.
[0028] The filler is a compound of calcium carbonate whisker and zinc oxide whisker.
[0029] Calcium carbonate whiskers were purchased from Shijiazhuang Xianghui Technology Co., Ltd.
[0030] Zinc oxide whiskers were purchased from Hangzhou Jikang New Materials Co., Ltd.
[0031] The modified petroleum coke powder is homemade, and the modification method of the modified petroleum coke powder is as follows: Step 1), 70kg of sulfuric acid and 30kg of phosphoric acid are mixed and cooled to obtain a composite acid, 50kg of petroleum coke powder is put into the composite acid at a constant temperature of 40°C, soaked and acidified for 4 hours for acidification, filtered, and the filter residue is taken, and the filter residue is washed with clean water until the pH value of the washing water is ≥6.5 to obtain acidified petroleum coke powder.
[0032] Step 2), 3 kg of isooctyl acrylate, 5.4 kg of bisphenol A bisallyl ether, 3 kg of phenyl tris(dimethylsiloxy)silane, and 75 kg of toluene are mixed to obtain a composite modified liquid, and the acidified petroleum coke powder is added to the composite modified liquid, kept at a constant temperature of 70°C, immersed for modification for 12 hours, filtered, and the filter residue is taken, and the filter residue is dried to obtain modified petroleum coke powder.
[0033] Sulfuric acid is commercially available, CAS number: 7664-93-9, concentration 60%.
[0034] Phosphoric acid is commercially available, CAS No.: 7664-38-2, concentration 60%.
[0035] Petroleum coke powder was purchased from Hebei Hengguang Mineral Products Co., Ltd., 60 mesh Isooctyl acrylate is commercially available, CAS number: 103-11-7.
[0036] Bisphenol A bisallyl ether is commercially available, CAS number: 3739-67-1.
[0037] Phenyltri(dimethylsiloxy)silane is commercially available, CAS number: 18027-45-7.
[0038] Toluene is commercially available, CAS number: 108-88-3.
[0039] The preparation method of the polytetrafluoroethylene composite material comprises the following steps: Step 01), 50kg polytetrafluoroethylene, 26kg modified petroleum coke powder, 22kg calcium carbonate whisker, and 2kg zinc oxide whisker are put into a stirring kettle at a speed of 120r / min, stirred for 10-15min, and mixed evenly to obtain a premix.
[0040] Step 02), the premix is subjected to cold pressing to obtain an embryo body, the cold pressing pressure is 50 MPa, and the holding time is 10 minutes.
[0041] Step 03), the embryo body is placed in a sintering furnace, heated to 330°C at a heating rate of 1°C / min, kept warm for 2 hours, sintered, and cooled to room temperature to obtain a polytetrafluoroethylene composite material.
[0042] Example 2 A polytetrafluoroethylene composite material comprises the following components: Polytetrafluoroethylene, modified petroleum coke powder, filler.
[0043] Polytetrafluoroethylene was purchased from Daikin, Japan, brand: F-303.
[0044] The filler is a compound of calcium carbonate whisker and zinc oxide whisker.
[0045] Calcium carbonate whiskers were purchased from Shijiazhuang Xianghui Technology Co., Ltd.
[0046] Zinc oxide whiskers were purchased from Hangzhou Jikang New Materials Co., Ltd.
[0047] The modified petroleum coke powder is homemade, and the modification method of the modified petroleum coke powder is as follows: Step 1), 75kg of sulfuric acid and 25kg of phosphoric acid are mixed and cooled to obtain a composite acid, 50kg of petroleum coke powder is put into the composite acid at a constant temperature of 45°C, soaked and acidified for 5 hours for acidification, filtered, and the filter residue is taken, and the filter residue is washed with clean water until the pH value of the washing water is ≥6.5 to obtain acidified petroleum coke powder.
[0048] Step 2), 3.3 kg of isooctyl acrylate, 5.7 kg of bisphenol A bisallyl ether, 3.3 kg of phenyl tris(dimethylsiloxy)silane, and 82.5 kg of toluene are mixed to obtain a composite modified liquid, and the acidified petroleum coke powder is added to the composite modified liquid, kept at a constant temperature of 75°C, immersed for modification for 13 hours, filtered, and the filter residue is taken, and the filter residue is dried to obtain modified petroleum coke powder.
[0049] Sulfuric acid is commercially available, CAS number: 7664-93-9, concentration 60%.
[0050] Phosphoric acid is commercially available, CAS No.: 7664-38-2, concentration 60%.
[0051] Petroleum coke powder was purchased from Hebei Hengguang Mineral Products Co., Ltd., 60 mesh Isooctyl acrylate is commercially available, CAS number: 103-11-7.
[0052] Bisphenol A bisallyl ether is commercially available, CAS number: 3739-67-1.
[0053] Phenyltri(dimethylsiloxy)silane is commercially available, CAS number: 18027-45-7.
[0054] Toluene is commercially available, CAS number: 108-88-3.
[0055] The preparation method of the polytetrafluoroethylene composite material comprises the following steps: Step 01), 55kg of polytetrafluoroethylene, 23kg of modified petroleum coke powder, 20.5kg of calcium carbonate whisker, and 1.5kg of zinc oxide whisker are put into a stirring kettle at a speed of 120r / min, stirred for 12.5min, and mixed evenly to obtain a premix.
[0056] Step 02), the premix is subjected to cold pressing to obtain an embryo body, the cold pressing pressure is 50 MPa, and the holding time is 10 minutes.
[0057] Step 03), the embryo body is placed in a sintering furnace, heated to 350°C at a heating rate of 1°C / min, kept warm for 2.5 hours, sintering is completed, and cooled to room temperature to obtain a polytetrafluoroethylene composite material.
[0058] Example 3 A polytetrafluoroethylene composite material comprises the following components: Polytetrafluoroethylene, modified petroleum coke powder, filler.
[0059] Polytetrafluoroethylene was purchased from Daikin, Japan, brand: F-303.
[0060] The filler is a compound of calcium carbonate whisker and zinc oxide whisker.
[0061] Calcium carbonate whiskers were purchased from Shijiazhuang Xianghui Technology Co., Ltd.
[0062] Zinc oxide whiskers were purchased from Hangzhou Jikang New Materials Co., Ltd.
[0063] The modified petroleum coke powder is homemade, and the modification method of the modified petroleum coke powder is as follows: Step 1), 80kg of sulfuric acid and 20kg of phosphoric acid are mixed and cooled to obtain a composite acid, 50kg of petroleum coke powder is put into the composite acid at a constant temperature of 50°C, soaked and acidified for 6 hours for acidification, filtered, and the filter residue is taken, and the filter residue is washed with clean water until the pH value of the washing water is ≥6.5 to obtain acidified petroleum coke powder.
[0064] Step 2), 3.6 kg of isooctyl acrylate, 6 kg of bisphenol A bisallyl ether, 3.6 kg of phenyl tris(dimethylsiloxy)silane, and 90 kg of toluene are mixed to obtain a composite modified liquid, and the acidified petroleum coke powder is added to the composite modified liquid, kept at a constant temperature of 80°C, immersed for modification for 14 hours, filtered, and the filter residue is taken, and the filter residue is dried to obtain modified petroleum coke powder.
[0065] Sulfuric acid is commercially available, CAS number: 7664-93-9, concentration 60%.
[0066] Phosphoric acid is commercially available, CAS No.: 7664-38-2, concentration 60%.
[0067] Petroleum coke powder was purchased from Hebei Hengguang Mineral Products Co., Ltd., 60 mesh Isooctyl acrylate is commercially available, CAS number: 103-11-7.
[0068] Bisphenol A bisallyl ether is commercially available, CAS number: 3739-67-1.
[0069] Phenyltri(dimethylsiloxy)silane is commercially available, CAS number: 18027-45-7.
[0070] Toluene is commercially available, CAS number: 108-88-3.
[0071] The preparation method of the polytetrafluoroethylene composite material comprises the following steps: Step 01), put 60kg polytetrafluoroethylene, 20kg modified petroleum coke powder, 19kg calcium carbonate whisker, and 1kg zinc oxide whisker into a stirring kettle, rotate at 120r / min, stir for 10-15min, mix evenly, and obtain a premix.
[0072] Step 02), the premix is subjected to cold pressing to obtain an embryo body, the cold pressing pressure is 50 MPa, and the holding time is 10 minutes.
[0073] Step 03), place the embryo body into a sintering furnace, heat to 380°C at a heating rate of 1°C / min, keep warm for 3 hours, complete sintering, and cool to room temperature to obtain a polytetrafluoroethylene composite material.
[0074] Comparative Example 1 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: The modified petroleum coke powder is homemade, and the modification method of the modified petroleum coke powder is as follows: Step 1), 3.3 kg of isooctyl acrylate, 5.7 kg of bisphenol A bisallyl ether, 3.3 kg of phenyl tris(dimethylsiloxy)silane, and 82.5 kg of toluene are mixed to obtain a composite modified liquid, 50 kg of petroleum coke powder is added to the composite modified liquid, the temperature is kept at 75 ° C, soaked for modification for 13 hours, filtered, the filter residue is taken, and the filter residue is dried to obtain modified petroleum coke powder.
[0075] Comparative Example 2 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite acid, hydrochloric acid is used to replace sulfuric acid in equal amounts.
[0076] Hydrochloric acid is commercially available, CAS number: 7647-01-0.
[0077] Comparative Example 3 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite acid, nitric acid is used to replace phosphoric acid in equal amounts.
[0078] Nitric acid is commercially available, CAS number: 7697-37-2.
[0079] Comparative Example 4 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite acid, hydrochloric acid is used to replace sulfuric acid in an equal amount, and nitric acid is used to replace phosphoric acid in an equal amount.
[0080] Hydrochloric acid is commercially available, CAS number: 7647-01-0.
[0081] Nitric acid is commercially available, CAS number: 7697-37-2.
[0082] Comparative Example 5 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite modified liquid, cyclohexyl methacrylate is used to replace isooctyl acrylate in equal amounts.
[0083] Cyclohexyl methacrylate is commercially available, CAS number: 101-43-9.
[0084] Comparative Example 6 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite modified liquid, allyl glycidyl ether is used to replace bisphenol A bisallyl ether in equal amounts.
[0085] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0086] Comparative Example 7 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite modified liquid, 3-isocyanatepropyltrimethoxysilane is used to replace phenyltri(dimethylsiloxy)silane in equal amounts.
[0087] 3-Isocyanatepropyltrimethoxysilane is commercially available, CAS number: 15396-00-6.
[0088] Comparative Example 8 A polytetrafluoroethylene composite material, compared with Example 2, the only difference is: In the composite modified liquid, cyclohexyl methacrylate is used to replace isooctyl acrylate in equal amounts, allyl glycidyl ether is used to replace bisphenol A bisallyl ether in equal amounts, and 3-isocyanate propyl trimethoxy silane is used to replace phenyl tris (dimethylsiloxane) silane in equal amounts.
[0089] Cyclohexyl methacrylate is commercially available, CAS number: 101-43-9.
[0090] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0091] 3-Isocyanatepropyltrimethoxysilane is commercially available, CAS number: 15396-00-6.
[0092] Experiment 1 According to GB / T3960-2016 "Test Method for Sliding Friction and Wear of Plastics", the wear quality of the samples made of the polytetrafluoroethylene composite materials of each embodiment and comparative example was tested. Dry friction was selected as the test condition.
[0093] The specific test data of Experiment 1 are as follows: Example 1: wear mass 1.2 mg; Example 2: wear mass 0.9 mg; Example 3: wear mass 0.8 mg; Comparative Example 1: wear mass 4.9 mg; Comparative Example 2: wear mass 3.9 mg; Comparative Example 3: wear mass 3.6 mg; Comparative Example 4: wear mass 4.2 mg; Comparative Example 5: wear mass 2.9 mg; Comparative Example 6: wear mass 2.4 mg; Comparative Example 7: wear mass 2.7 mg; Comparative Example 8: Wear mass 3.3 mg.
[0094] According to the data comparison of each embodiment and the comparative example, it can be obtained that the wear quality of each embodiment is significantly lower than that of each comparative example. In comparative example 1, the acidification step is cancelled, and only the modifying liquid is used to modify the petroleum coke powder, and the obtained modified petroleum coke powder has a poor effect on improving the wear resistance of the polytetrafluoroethylene material; in comparative examples 2-4, other acids are used to replace the sulfuric acid and phosphoric acid in the embodiment alone or in whole, which destroys the compounding system of sulfuric acid and phosphoric acid, resulting in that it is difficult to form a special structure and produce special functional groups on the surface of the acidified petroleum coke powder, which leads to a decrease in the effect of subsequent modification with the modifying liquid, which leads to a significant decrease in the effect of improving the wear resistance of polytetrafluoroethylene compared with the embodiment; in comparative examples 5-8, other modified raw materials are used to replace the isooctyl acrylate, bisphenol A bisallyl ether, and phenyl tris(dimethylsiloxane) silane in the embodiment alone or in whole, which destroys the special modifying liquid system, resulting in a decrease in the modification effect, which leads to a decrease in the effect of improving the wear resistance of the polytetrafluoroethylene material.
[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polytetrafluoroethylene composite material, characterized in that: The composition includes the following components in parts by weight: 50-60 parts of polytetrafluoroethylene; 20-26 parts of modified petroleum coke powder; 20-24 parts of filler; The modification method of the modified petroleum coke powder is as follows: Step 1), adding petroleum coke powder into a composite acid for acidification, filtering, and obtaining acidified petroleum coke powder; Step 2), adding the acidified petroleum coke powder into the composite modification liquid, filtering, and drying to obtain modified petroleum coke powder; The composite acid is a compound of sulfuric acid and phosphoric acid; The composite modified liquid is a compound of isooctyl acrylate, bisphenol A bisallyl ether, phenyl tris(dimethylsiloxane) silane and toluene.
2. A polytetrafluoroethylene composite material according to claim 1, characterized in that: In the composite acid, the mass ratio of sulfuric acid to phosphoric acid is 7-8:2-3.
3. A polytetrafluoroethylene composite material according to claim 2, characterized in that: In the composite modified liquid, the mass ratio of isooctyl acrylate, bisphenol A bisallyl ether, phenyl tris(dimethylsiloxy)silane and toluene is 1-1.2:1.8-2:1-2:25-30.
4. The polytetrafluoroethylene composite material according to claim 1, characterized in that: The filler is a compound of calcium carbonate whisker and zinc oxide whisker.
5. The polytetrafluoroethylene composite material according to claim 4, characterized in that: The mass ratio of the calcium carbonate whisker to the zinc oxide whisker is 19-22:1-2.
6. The polytetrafluoroethylene composite material according to claim 1, characterized in that: In the step 1), after the petroleum coke powder is put into the composite acid, the temperature is kept at 40-50° C. and the mixture is soaked and acidified for 4-6 hours.
7. The polytetrafluoroethylene composite material according to claim 1, characterized in that: In the step 2), the acidified petroleum coke powder is put into the composite modification liquid, and then the temperature is kept at 70-80° C. and the modified liquid is immersed for 12-14 hours.
8. A method for preparing the polytetrafluoroethylene composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 01), polytetrafluoroethylene, modified petroleum coke powder and filler are uniformly mixed to obtain a premix; Step 02), the premix is subjected to cold pressing to obtain an embryo body; Step 03), sintering the embryo at 330-380°C and cooling to obtain a polytetrafluoroethylene composite material.